Analisis Kebutuhan Tenaga Keperawatan Dengan Metode Workload Indicator Staff Need (WISN) Di Ruang Rawat Inap RSUD dr. R.M. Djoelham Binjai - Muhammad Lutfi Arafandi; Nur Aini; Ramadhani Syafitri Nasution (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The WISN method is a resource management tool that calculates staff needs based on workload for certain staff categories and clearly the facility and type of health facility. This tool can be applied nationally, regionally, in health facilities, namely it is easy to use both technically, comprehensive, realistic and makes it easy to determine variations in human resource needs in various types of health services such as community health centers and hospitals. The aim of this research is to analyze the need for nursing staff based on workload using the Workload Indicator Staff Need (WISN) method in the Inpatient Room at RSUD dr. R.M. Djoelham Binjai in 2023. The research design used was descriptive research using observational techniques. The population in this study were all nurses in the Inpatient Room at RSUD dr. R.M. Djoelham Binjai, numbering 61 nurses, this population sampling was carried out using purposive sampling. The number of samples to be studied was 61 people. Data analysis was carried out using the WISN analysis. After the data was obtained from filling out the questionnaire by the researcher based on observations, recording and adjustments were made to the work documentation carried out by the nursing staff in the Inpatient Room. The results of research based on WISN method calculations show that the need for nursing staff in the Inpatient Room at RSUD dr. R.M. Djoelham Binjai still lacks 3 nursing staff. The conclusion was that there was an influence between working time, activities of nursing staff, workload standards, slack factors and calculations of nursing staff needs for nursing staff on the need for nursing staff in the Inpatient Room at RSUD dr. R.M. Djoelham Binjai, it is recommended that the Head of the Inpatient Room need to evaluate the division of tasks so that the nursing service process can be carried out well and improve the quality of service in the Inpatient Room at RSUD dr. R.M. Djoelham Binjai